LEADERSHIP TRAITS OF NURSE MANAGERS AND NURSE STAFF COMMITMENT IN THE PHILIPPINES HOSPITALS - Abdulmalik, Paida P.; Pangandaman, Hamdoni (Universitas Airlangga, 2024)
Background: Effective nurse leadership significantly influences healthcare service quality. Nurse managers' leadership impacts staff nurse commitment, patient outcomes, and organizational success. Aims: To examine nurse manager leadership traits and their relationship with staff nurse commitment in a government hospital. Methods: Descriptive-inferential correlation research with stratified and randomized nurse managers (n = 21) and staff nurses (n = 117) as participants from five selected hospitals at Lanao del Norte. Adopted questionnaires on leadership traits and commitment were used and data were analyzed using frequency, percentage, mean, and standard deviation in SPSS v.25. Results: The result shows that nurse manager leadership qualities are usually valid for a leader who encourages others to do what is right, gives subordinates continuing education, and is an ethical and self-confident leader. Their staff nurses believed positive components of the leadership traits of nurse managers were sometimes true. Staff nurses were generally still deciding whether they were committed to their work effectively, continuously, or normatively. Nurse managers' leadership traits are significantly related to the staff nurses' affective, continuance, and normative commitment. Conclusion: Fostering positive leadership through education and supportive environments enhances staff nurse commitment and job satisfaction, reducing nurse turnover and improving nursing care quality. Keywords: commitment, leadership traits, leadership qualities, nurse manager, nurse staff